2015
DOI: 10.1186/s12977-015-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 immune activation induces Siglec-1 expression and enhances viral trans-infection in blood and tissue myeloid cells

Abstract: BackgroundMyeloid cells are key players in the recognition and response of the host against invading viruses. Paradoxically, upon HIV-1 infection, myeloid cells might also promote viral pathogenesis through trans-infection, a mechanism that promotes HIV-1 transmission to target cells via viral capture and storage. The receptor Siglec-1 (CD169) potently enhances HIV-1 trans-infection and is regulated by immune activating signals present throughout the course of HIV-1 infection, such as interferon α (IFNα).Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 42 publications
(63 reference statements)
1
82
1
1
Order By: Relevance
“…These authors also detected large amounts of internalized HIV-1 particles by confocal microscopy and suggested that this may reflect a "dead end" for functional retroviral particles. However, although neither lysosomal nor proteasomal inhibitors could prevent the apparent loss of MLV structural proteins over time in BMDM, lysosomal inhibitors did prevent the degradation of cell-associated HIV-1 in human macrophages (63).…”
Section: Discussionmentioning
confidence: 83%
“…These authors also detected large amounts of internalized HIV-1 particles by confocal microscopy and suggested that this may reflect a "dead end" for functional retroviral particles. However, although neither lysosomal nor proteasomal inhibitors could prevent the apparent loss of MLV structural proteins over time in BMDM, lysosomal inhibitors did prevent the degradation of cell-associated HIV-1 in human macrophages (63).…”
Section: Discussionmentioning
confidence: 83%
“…The basal level of ISGs was higher than in IDCs due to the process of maturation, as has been described previously (48). However, HIV-1 infection under restrictive conditions (ϪVpx) of MDCs further increased different ISGs (63). Induction levels varied among the measured ISGs, and in some cases differences were not statistically significant due to the variability found among different donors, but trends were consistent.…”
Section: Chemokine Expression During MDC Infectionmentioning
confidence: 51%
“…Paradoxically, in the particular case of HIV infection, a normal immune response like chemokine production would result in higher rate of trans-infection due to the high susceptibility to infection of CD4 lymphocytes in the immune synapse. Actually, it has been previously described (63) that the increase of IFN-␣ production by DCs results in higher expression of SIGLEC-1, which in turns causes an enhancement of HIV infection of CD4 ϩ T lymphocytes. In this article we describe another mechanism, chemokine production, that contributes to enhancement of HIV infection and dissemination in the immune synapse.…”
Section: Chemokine Expression During MDC Infectionmentioning
confidence: 99%
“…This interaction between Siglec-1 and GM3 is independent of the HIV envelope protein [22] , while in macrophages the capture of HIV-1 is through the interaction of Siglec-1 and HIV-1 envelope protein [15,16] . Studies have shown that Siglec-1 expression is influenced by the cytokines present in the environmental milieu induced as a result of chronic inflammation [23,24] . Upregulation of Siglec-1 on human and nonhuman primate monocytes after HIV-1 or SIV infection respectively, has been demonstrated early after infection and then an increase as the disease progresses to the chronic phase [25,26] .…”
Section: Research Highlightmentioning
confidence: 99%